Analisis Pengaruh Investasi Infrastruktur Publik Terhadap Pertumbuhan Ekonomi di Aceh - Fikriah Fikriah; Meta Wulandari (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2015)
This study was intended to see how the effects of public infrastructure investment to economic growth in 23 districts and municipalities in Aceh province. The independent variables consist of investments in roads, electricity and clean water while economic growth assigned as dependent variable. Cobb-Douglas producation function with panel data analysis method in which the data used is the data from 2008 to 2012. The research results showed that by using a data processing eviews 7 shows the positive effect the investment variables with p value = 0.00530.05, so it can be said that investment in road infrastructure significantly influence economic growth in 23 districts/cities of Aceh province, while infrastructure investment electricity and clean water effect with a significant level of 10 percent to economic growth in the 23 districts/cities of Aceh province. See the role of roads, electricity and clean water as an essential requirement in the life of society, the government should provide more for infrastructure investment in these sectors in order to increase economic growth.